Sosialisasi Perilaku Aman Pejalan Kaki dan Pengendara Sepeda Siswa Sekolah - Darunanto, Danang; Subandi, Subandi; Saidah, Deslida; Wahyuni, Rr. Endang; Nur, Yunitha Ardiana (Institut Transportasi dan Logistik Trisakti, 2023)
This community service activity aims to raise awareness among students who use bicycles or walk to be more vigilant on their way to and from school. The participants of the activity are students of SMPN 10 Central Jakarta. The school is at SMPN 10, Jalan Sumur Batu Raya Number 1, RT/RW 03/01, Kemayoran District, Central Jakarta Special Capital Region 10640. The main impact of this activity is that participants are expected to understand how pedestrians and cyclists should behave on the road for their safety and the safety of other road users. The target achievement of this educational activity is for more students to understand the standard crossing procedures 4T and the support of the School Safety Zone (ZoSS), so that students will behave correctly when walking on the road and at crossing points, and there will be encouragement to change their lifestyle from using other forms of transportation to becoming bicycle users.